Sistemática e ecologia de ácaros Erythraeoidea (Acari: Parasitengona) - Samuel Geremias dos Santos Costa (2019)
During their life cycle Parasitengona go throught an egg, a regressive calyptostaic prelarva, a heteromorphic ectoparasitic larva, a calyptostatic protonymph, free-living predaceous deutonymph, a calyptostatic tritonymph and a free-living predaceous adult. This complex life cycle requires rearing or molecular barcoding association of heteromorphic instars. The necessity of using those technics and the difficults associated with them, made most of the described species known from either post larval instars or larva. In the first chapter of this study, two new cave dwelling Erythraeidae (Acari: Parasitengona) species are described including all active instars and a possibly troglomorphic sepecies. Additionally, a complete description of the adults and deutonymph of Charletonia rocciai Treat & Flechtmann, 1979 and notes on the larval morphology and behavior are provided. The instar association were made through rearing experiments and molecular analysis employing the mitochondrial cytochrome oxidase I (COI) gene and the Bayesian Generalized Mixed Yule Coalescent (bGMYC) algorithm for species delimitation. We also demonstrated experimentally that C. rocciai larvae are not attached to the same host during the entire stage, being able to swap from a host insect to another. The presence of troglomorphism and the distribution of the specimens in the cave or epigean environment are also discussed. In the second chapter of the present study a taxonomic investigation on the smaridid genus Trichosmaris Southcott, 1963 led to the description, for the first time, of its larval instar. Larvae and post-larval instars were associated by rearing to T. dispar Southcott, 1963 and a new Trichosmaris species. They are described along an additional new species from the southeast of Brazil and a key for Smarididae genera and for Trichosmaris species. Phylogenetic relationships among Smarididae are inferred based on forty-nine morphological characters from larvae and adults, including all species for which the larvae are known. The evolution of a highly modified gnathosoma for larval Smarididae and a possible predatorial behavior is discussed. In addition, synonymies and new combinations proposed.